2017
DOI: 10.5089/9781484303689.001
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Reforms, Long-term Growth and Income Inequality

Abstract: We estimate the effects on growth of nine fiscal reform episodes in seven high-income countries using the Synthetic Control Method. These episodes are selected using an indicator-based approach applied to the evaluation of growth-friendly fiscal reforms during 1975-2010. We find that in reform countries the annual growth rate of real GDP was on average about 1 percentage point above their synthetic units 10 years after each respective reform. Moreover, countries which were initially less developed seemed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Campagne and Poissonnier (2017) determined, using the DSGE model, that real sector reforms, as measured by production market regulations, increased growth and decreased inequalities in the short and long run. Using the SCM (Synthetic Control Method) model, Ormaechea et al (2017) found that scal sector reforms, as measured by taxation and public expenditure regulations, increased growth but did not impact inequality. Contrary to the predictions of neoclassical theories, Brancaccio et al (2018) determined with the OLS model that real sector reforms, measured by the OECD (Employment Protection Legislation Index), had no effect on growth and reduced inequalities in 23 OECD member countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Campagne and Poissonnier (2017) determined, using the DSGE model, that real sector reforms, as measured by production market regulations, increased growth and decreased inequalities in the short and long run. Using the SCM (Synthetic Control Method) model, Ormaechea et al (2017) found that scal sector reforms, as measured by taxation and public expenditure regulations, increased growth but did not impact inequality. Contrary to the predictions of neoclassical theories, Brancaccio et al (2018) determined with the OLS model that real sector reforms, measured by the OECD (Employment Protection Legislation Index), had no effect on growth and reduced inequalities in 23 OECD member countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this way, the literature on the effects of reforms on growth or inequality can be expanded, and the possible trade-off between growth and inequality reforms in Turkey may be identi ed. There are, to the best of our knowledge, a small number of empirical studies that examine the trade-off effects of reform, growth, and inequality, including Campagne and Poissonnier (2017), Ormaechea et al (2017), Brancaccio et al (2018), Ostry et al (2021), and . The fourth and nal contribution is to examine the effects of reforms on growth and inequality using the A-ARDL model, which is novel and was developed to overcome possible endogeneity problems in time series, in contrast to the studies in the literature, which typically examine the effects of reforms on growth and inequality within the context of panel data analysis.…”
mentioning
confidence: 99%
“…Tsounta and Ouseke [7] claim that higher tax revenues are important contributor to recent reduction in income inequality in Latin America. Moreover, Acosta-Ormaechea et al [42] find that inequality is not affected by the growth-friendly fiscal reforms. Finally, Chen and Tsai [10] report capital incentives don't significantly contribute to Gini coefficient.…”
Section: Literature Reviewmentioning
confidence: 99%